Epistemological Remediation's in Enabling Sociological Research: Critical Analytical Study - Ali, Hatem (Al-Adab Journal, 2023)
The study asked, as follows: What are epistemological perceptions? What are its indicators in the current Iraqi sociological research? which led to more specific questions, what is the theoretical remediation and what is the methodological remediation in the theses and theses approved in the universities of Baghdad and Qadisiyah? The aim of the study was to identify the research problems related to the theoretical and methodological construction of theses and theses and the alternatives that are included in that, so the study required the selection of a sample of theses and theses, by (25), according to a period of time at the last five years, until the completion of the current study, in addition to taking into account gender (researchers / researchers). The study concluded to clarify a number of research problems, and then extract a set of reflections as alternatives within the structure of these problems, to enable theoretical and methodological construction in Iraqi sociological research.